S-QUASI-INJECTIVE MODULES - Abud, Ahmed Hanoon (Al-Nahrain Journal of Science, 2010)
Let R be a ring with non-zero identity and let M be a right R-module. This paper study theconcept of s-quasi-injectivity. Some properties of this concept are investigated and some conditionshas been given for s-quasi-injective R-modules to be injective or quasi-injective. Some conditionsstated for submodules with this property to be s-quasi-injective.